How to deal with anger: A psychology and Islamic perspective - Faizah; Mukjizah Mukhtar Lutfi; Abdul Haris (AMCA Journal of Community Development, 2021)
Anger management is a strategy used to minimize the emotional and physiological impacts that arise from anger. Managing anger involves a complex interaction between thoughts, feelings, behavior, and physiology. Anger management is considered important from the perspective of psychology and an Islamic perspective, so it is essential to pay attention to the study of anger management in both perspectives. This study uses a systematic literature review method by examining anger management from psychology and Islam. The results show that anger management is seen in line with a psychological and Islamic perspective as an appropriate strategy to respond to anger to be something more positive and environmentally acceptable. However, in practice, the psychological perspective is more oriented towards controlling emotions through more general techniques such as behavior-changing techniques and cognitive restructuring. From an Islamic perspective, its application tends to lead to emotional control through spiritual activities such as ablution, dhikr, prayer, and reading the Al-Quran.